Extreme river flood exposes latent erosion risk - H. J. Barneveld; R. M. Frings; E. Mosselman; J. G. Venditti; M. G. Kleinhans; A. Blom; R. M. J. Schielen; W. H. J. Toonen; D. Meijer; A. J. Paarlberg; R. P. van Denderen; J. S. de Jong; et al. (Nature, 2025)
Abstract Climate change is expected to increase the frequency and magnitude of river floods 1 . Floods not only cause damage by inundation and loss of life 2,3 but also jeopardize infrastructure because of bank failure and riverbed erosion processes that are poorly understood. Common flood safety programmes include dyke reinforcement and river widening 4–9 . The 2021 flood in the Meuse Basin caused 43 fatalities and billions of dollars of damage to infrastructure 10 . Here, on the basis of analysis of the Meuse flood, we show how uneven widening of the river and heterogeneity of sediment deposits under the river can cause massive erosion. A recent flood safety programme widened the river 11 , but created bottlenecks where widening was either prevented by infrastructure or not yet implemented. Riverbed erosion was exacerbated by tectonic uplift that had produced a thin top gravel layer above fine-grained sediment. Greatly enhanced flow velocities produced underwater dunes with troughs that broke through the gravel armour in the bottlenecks, exposing easily erodible sands, resulting in extreme scour holes, one more than 15 m deep. Our investigation highlights the challenges of re-engineering rivers in the face of climate change, increased flood risks and competition for river widening space, and calls for a better understanding of the subsurface.